Moderation In Fatwas And Ijtihad:An Analysis Of Fatwas Issued By The Mki Malaysia Concerning The Covid-19 Pandemic - Abdul Manan Ismail; Ahmad Syukran Baharuddin (Universitas Islam Negeri Syarif Hidayatullah Jakar, 2024)
Indexed by Scopus